Iron, Zinc, and Calcium Bioavailability of Nutrient-Dense Foods for Designated Complementary Feeding of Children Under Two in East Nusa Tenggara - Sanjiwani, Putu Amrytha; Fahmida, Umi; Santoso, Muhayatun; Marliyati, Sri Anna; Mansyur, Muchtaruddin (Universitas Airlangga, 2026)
Background: Inadequate quantity and quality of complementary feeding contribute substantially to micronutrient deficiencies, particularly iron, zinc, and calcium. In Indonesia, intake of these micronutrients is frequently suboptimal, and their bioavailability is often compromised by dietary inhibitors, primarily phytate. Objective: This study aimed to compare the in vitro bioavailability of iron, zinc, and calcium from selected locally available animal-and plant-source foods with potential for promotion in complementary feeding among children aged 6–24 months, and to evaluate the effects of pre-processing treatments on micronutrient bioavailability and phytate reduction. Method: A laboratory-based experimental study was conducted to assess the micronutrient bioavailability and phytate content in sticky corn, mung beans, cowpeas, and moringa leaf subjected to soaking (24 h), boiling, and germination (72 h). Bioavailability was analyzed using a solubility-based in vitro digestion model. Anchovy and chicken liver served as animal-source comparators. Result: Pre-processing treatments significantly reduced phytate content in mung beans, cowpeas, and sticky corn (p < 0.001), with germination yielding the greatest reduction. However, desirable calcium bioavailability was not achieved in germinated cowpeas and sticky corn. Anchovy and chicken liver exhibited substantially higher iron, zinc, and calcium bioavailability compared with plant-source foods. Conclusion: Germination of plant-source foods enhances iron, zinc, and calcium bioavailability; however, their bioavailability remains lower than that of animal-source foods. Further studies are needed to determine the optimal animal-to-plant-source food ratios for the development of nutrient-dense complementary foods that meet iron, zinc, and calcium requirements.